Teacher Round Table—A Conversation Inspired by Urquhart & Urquhart’s “Fahrenheit 450 - Shelly Unsicker-Durham; Jennifer Guyor-Jowett; Jessica Wiley; Christine DeStefano (Study and Scrutiny, 2025)
Study and Scrutiny’s third Teacher Round Table focuses on an article from S&S Issue 6.1 by Zach Urquhart and Pearson Urquhart, “Fahrenheit 450: A Conversation through Poem Used to ‘Cool Down’ the Discussion of Banned and Controversial Books.” As book bans continue across the country, it feels important to talk with one another about what this issue looks like in different schools and districts and to consider possible approaches for navigating such a time in our collective history. Three educators, passionate about literacy, classroom practice, and the students they teach, joined Shelly Unsicker-Durham to consider the poetic exchange between a researcher/father and an activist/daughter and the lessons we might carry back to our classrooms.